The misadventures of Salem Hyde. 1, Spelling trouble - Cammuso, Frank (Cammuso, Frank. Misadventures of Salem Hyde., 2013)
To help her stay out of trouble, her parents find young witch Salem Hyde an animal companion, Percival J. Whamsford III. They do not much like each other, but when Salem enters the school spelling bee and tries to "spell" her way to victory, she needs Whammy's help.